Fibroblast growth factor and hepatocyte growth factor in adolescents with juvenile idiopathic arthritis treated with methotrexate - Pavlova, Olga (ScienceRise: Medical Science, 2020)
Methotrexate (MTX) is a cornerstone of therapy worldwide for juvenile idiopathic arthritis (JIA). Despite the fact that fibrosis molecular mechanisms as well as MTX elimination and fibrosis indexes were studied a lot there is still not enough information for adolescence. The aim was to study dynamics of molecular-cellular mechanisms activation of fibrotic processes development in the liver in adolescents with juvenile idiopathic arthritis treated with methotrexate by determining the content of fibroblast growth factor and hepatocyte growth factor. Materials and methods: A total of 68 children with juvenile idiopathic arthritis, were enrolled in the study. 25 boys (36.8 %) and 43 girls (63.2 %) were examined. Children were divided into four groups in accordance with cumulative dose (CD) of methotrexate. The following data were analyzed: liver function tests (aspartate aminotransferase (AST) (U/L), alanylaminotransferase (ALT) (U/L)), lactate dehydrogenase (LDH) (U/L), adiponectin (μg / ml), BFGF (pg / ml), HGF (pg / ml), liver fibrosis indexes APRI and FIB-4 Score. Results. Positive effect of JIA treatment with MTX on the liver is noted. When CD MTX reaches 1 and3 grams, liver state studying is needed. When the CD MTX of1 gram is reached, regulatory mechanisms are involved that provoke liver regeneration. When the CD MTX reaches3 grams, the liver condition may deteriorate, which in the future can lead to irreversible processes of liver fibrosis. Conclusions: Thus, it is important to control possible liver disorders in adolescence treated with MTX. Monitoring the processes of liver fibrosis is appropriate at all stages of JIA treatment, but it is most advisable when the MTX cumulative dose is reaching 1 and3 grams